Buddhist philosophy : a comparative approach - Emmanuel, Steven M. (Hoboken : Wiley, 2017)
Buddhist Philosophy: A Comparative Approach presents a series of readings that examine the prominent thinkers and texts of the Buddhist tradition in the round, introducing contemporary readers to major theories and debates at the intersection of Buddhist and Western thought. -Takes a comparative, rather than oppositional, approach to Buddhist philosophy, exploring key theories and debates at the intersection of Eastern and Western thought -Addresses a variety of topics that represent important points of convergence between the Buddhist and Western philosophical traditions -Features contributions from a wide array of acclaimed international scholars in the discipline -Provides a much-needed cross-cultural treatment of Buddhist philosophy appropriate for undergraduate students and specialists alike.
Editor's Introduction / Steven M Emmanuel -- Buddhist Philosophy as a Way of Life / Christopher W Gowans -- The Other Side of Realism / Douglas Duckworth -- Emergentist Naturalism in Early Buddhism and Deweyan Pragmatism / John J Holder -- Metaphysical Dependence, East and West / Ricki Bliss, Graham Priest -- Metaphysics and Metametaphysics with Buddhism / Tom JF Tillemans -- Are Reasons Causally Relevant for Action? Dharmakīrti and the Embodied Cognition Paradigm / Christian Coseru -- Zen's Nonegocentric Perspectivism / Bret W Davis -- Rhetoric of Uncertainty in Zen Buddhism and Western Literary Modernism / Steven Heine -- From the Five Aggregates to Phenomenal Consciousness / Jake H Davis, Evan Thompson -- Embodying Change / Erin A McCarthy -- Buddhist Modernism and Kant on Enlightenment / David Cummiskey -- Compassion and Rebirth / John Powers.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Buddhist philosophy; Buddhist philosophy; PHILOSOPHY / Eastern; Electronic books